Multifunctional approaches to provide potential pharmacophores for the pharmacy shelf: Heracleum sphondylium L. subsp. ternatum (Velen.) Brummitt. (February 2019) - Uysal, Ahmet; Ozer, Omer Yilmaz; Zengin, Gokhan; Stefanucci, Azzurra; Mollica, Adriano; Picot-Allain, Carene Marie Nancy; Mahomoodally, Mohamad Fawzi
Graphical abstract: Highlights: Evaluation of the biological properties of Heracleum sphondylium L. subsp. ternatum (Velen.) Brummitt . Methanol and ethyl acetate extracts of H. sphondylium showed pronounced inhibition effects on tested enzymes. Chlorogenic acid was identified as the main component of the methanol extract. The extracts did not cause mutation of bacterial strains and showed potent antimutagenic capacity. This study provides valuable baseline data on H. sphondylium for the development of novel therapeutic agents. Abstract: Heracleum sphondylium L. subsp. ternatum (Velen.) Brummitt. commonly known as "hogweed" is traditionally used to manage several human ailments. This investigation assessed, for the first time, the enzyme inhibitory properties, antioxidant activity, phytochemical profile, antimutagenic, and antimicrobial potential of the ethyl acetate, methanol, and water extracts of H. sphondylium . We also established the possible interactions of identified phenolic compounds with cholinesterases, amylase, glucosidase, and tyrosinase using in silico docking studies. Chlorogenic acid was found in high amounts in the methanol extract of H. sphondylium . The methanol extract was an effective inhibitor of acetylcholinesterase (1.70 mg galantamine equivalent (GALAE)/g extract) while the ethyl acetate extract showed pronounced inhibitory action against butyrylcholinesterase (1.77 mg GALAE/g extract). The extracts exhibited low inhibition against amylase (0.12-0.84 mmol acarbose equivalent (ACAE)/g extract) and a more pronounced inhibition against glucosidase (2.29–3.65 mmol ACAE/g extract). In silico results showed that rutin and quercetin (-70.4 and -72.2 Kcal/mol, for rutin and quercetin respectively) docked to the enzymatic cavity of acetylcholinesterase but these phenolic compounds showed less affinity with butyrylcholinesterase (-15.0 and -5.2 Kcal/mol, for rutin and quercetin respectively). The extracts did not induce any mutations on the bacterial strains, while they have excellent antimutagenic capacity against well-known mutagens (inhibition values 98%, 97% and 96%). The methanol extract (0.78 mg/ml) showed moderate antifungal activity while the ethyl acetate extract (0.78–3.12 mg/ml) showed weak to moderate antimicrobial activity. This study provides valuable baseline data which might serve for the development of future pharmacophores for the management of human ailments.